Diagnosis and management of common non-viral oral ulcerations - Willie van Heerden; S.C. Boy (South African Family Practice)
Oral ulcerations are common lesions encountered in private practice. Oral ulcers can have a localised aetiology or be a manifestation of a variety of systemic conditions or disorders. Appropriate management depends on the correct diagnosis which can at times be difficult due to similar clinical features. The aetiology, diagnosis and management of the most common non-viral ulcerative disorders of the oral mucosa are discussed. These include traumatic ulcers, recurrent aphthous stomatitis, malignancy as well as oral ulceration associated with cutaneous pathology.